Towards unravelling biological mechanisms behind radiation-induced oral mucositis via mass spectrometry-based proteomics - Subedi, Prabal; Huber, Katharina; Sterr, Christoph; Dietz, Anne; Strasser, Lukas; Kaestle, Felix; Hauck, Stefanie M.; Duchrow, Lukas; Aldrian, Christine; Monroy Ordonez, Elsa Beatriz; Luka, Benedikt; Thomsen, Andreas R.; et al. (Frontiers in Oncology, 2023)
Objective: Head and neck cancer (HNC) accounts for almost 850,000 new cases per year. Radiotherapy (RT) is used to treat the majority of these patients. A common side-effect of RT is the onset of oral mucositis, which decreases the quality of life and represents the major dose-limiting factor in RT. To understand the origin of oral mucositis, the biological mechanisms post-ionizing radiation (IR) need to be clarified. Such knowledge is valuable to develop new treatment targets for oral mucositis and markers for the early identification of “at-risk” patients. Methods: Primary keratinocytes from healthy volunteers were biopsied, irradiated in vitro (0 and 6 Gy), and subjected to mass spectrometry-based analyses 96 h after irradiation. Web-based tools were used to predict triggered biological pathways. The results were validated in the OKF6 cell culture model. Immunoblotting and mRNA validation was performed and cytokines present in cell culture media post-IR were quantified. Results: Mass spectrometry-based proteomics identified 5879 proteins in primary keratinocytes and 4597 proteins in OKF6 cells. Amongst them, 212 proteins in primary keratinocytes and 169 proteins in OKF6 cells were significantly differentially abundant 96 h after 6 Gy irradiation compared to sham-irradiated controls. In silico pathway enrichment analysis predicted interferon (IFN) response and DNA strand elongation pathways as mostly affected pathways in both cell systems. Immunoblot validations showed a decrease in minichromosome maintenance (MCM) complex proteins 2-7 and an increase in IFN-associated proteins STAT1 and ISG15. In line with affected IFN signalling, mRNA levels of IFNβ and interleukin 6 (IL-6) increased significantly following irradiation and also levels of secreted IL-1β, IL-6, IP-10, and ISG15 were elevated. Conclusion: This study has investigated biological mechanisms in keratinocytes post-in vitro ionizing radiation. A common radiation signature in keratinocytes was identified. The role of IFN response in keratinocytes along with increased levels of pro-inflammatory cytokines and proteins could hint towards a possible mechanism for oral mucositis.